Pendidikan Mitigasi Bencana Sekolah Menengah Pertama di Kabupaten Bondowoso - Ismawandi Bripandika Putra; Acmad Nuriyadi; Santika Rentika Hadi; Dharma Utama; Angga Indra Kusuma; Gatot Margisal Utomo; Mohammad Hanafi (Kanigara, 2023)
School is an effective means of providing studying about disaster management, especially for schools located in disasterprone areas. In carrying out education about disaster management, it can indeed be started from elementary school age, because that way children areable to know a natural disaster occurs. The method of implementing activities is in the form of exploratory discussions. Results, knowledge about disaster management in the school environment is needed by all residents in the school, so that they understand about natural disasters, attitudes in dealing with disasters, the importanceof protecting the surrounding environment, and when disaster occurs, they are able to anticipate and prepare themselves, so that it will reduce the impact when a disaster occurs